The Attractiveness of CEE Countries For FDI. A Public Policy Approach Using the Topsis Method - Andreea PAUL; Ana Cristina POPOVICI; Cantemir Adrian CĂLIN (Transylvanian Review of Administrative Sciences, 2014)
This paper analyzes the location decision for foreign direct investments (FDI) in Central and Eastern European (CEE) countries based on the attractiveness of policies most influenced by public officials. Our assessment of the FDI inflows in a country is based on four pillars: infrastructure, quality of institutions, labor market and taxes. The attraction degree of the CEE countries in 2007 and 2010 is calculated using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method, a tool usually used for decision-making issues. The empirical result indicates that Estonia is the most attractive country for investments (as regards the public policy approach). Globally, the paper establishes the state’s role in attracting FDI and identifies whether there is room for further improvement on the public policy side.